Citizen Science Observation of a Gamma‐Ray Glow Associated With the Initiation of a Lightning Flash - Tsurumi, M.; Enoto, T.; Ikkatai, Y.; Wu, T.; Wang, D.; Shinoda, T.; Nakazawa, K.; Tsuji, N.; Diniz, G. S.; Kataoka, J.; Koshikawa, N.; Iwashita, R.; et al. (Geophysical research letters, 2023)
Gamma‐ray glows are observational evidence of relativistic electron acceleration due to the electric field in thunderclouds. However, it is yet to be understood whether such relativistic electrons contribute to the initiation of lightning discharges. To tackle this question, we started the citizen science “Thundercloud Project,” where we map radiation measurements of glows from winter thunderclouds along Japan's sea coast area. We developed and deployed 58 compact gamma‐ray monitors at the end of 2021. On 30 December 2021, five monitors simultaneously detected a glow with its radiation distribution horizontally extending for 2 km. The glow terminated coinciding with a lightning flash at 04:08:34 JST, which was recorded by the two radio‐band lightning mapping systems, FALMA and DALMA. The initial discharges during the preliminary breakdown started above the glow, that is, in vicinity of the electron acceleration site. This result provides one example of possible connections between electron acceleration and lightning initiation. Plain Language Summary Thunderstorms are natural particle accelerators. The strong electric field inside thunderclouds accelerates relativistic electrons, which emit gamma rays via interaction with the atmosphere. High‐energy photons generated in this process have been observed as radiation enhancements called gamma‐ray glows. Winter thunderclouds along the sea of Japan are an ideal target for monitoring glows because their altitudes are usually sufficiently low for the generated gamma‐ray photons to reach the ground. We started a new citizen science “Thundercloud Project” in this area, where we distributed radiation detectors to citizen supporters to observe glows and to reveal their relationship with the aerological condition and lightning discharges. On 30 December 2021, five of those sensors detected a glow from a single thundercloud. Two of them recorded a sudden termination of the glow coinciding with a lightning flash, which was monitored by our two radio mapping systems of FALMA and DALMA. The initial discharges of the flash started at a location about 1.6 km above the glow region with an unusually fast downward progression. This paper is the first report of our citizen science project. We discuss the possibility that accelerated electrons contribute to the initiation of lightning discharges. Key Points We started the citizen science “Thundercloud Project,” a multi‐point observation campaign of gamma‐ray glows from thunderstorms On 30 December 2021, five radiation monitors detected a 2‐km‐long size gamma‐ray glow, which suddenly terminated with a lightning flash Two radio mapping systems of lightning identified the initiation of the discharges, which started at a location above the glow region